Screening and support for emotional burdens of youth with type 1 diabetes: Strategies for diabetes care providers. Issue 3 (22nd September 2017) - Hilliard, Marisa E; De Wit, Maartje; Wasserman, Rachel M; Butler, Ashley M; Evans, Meredyth; Weissberg‐Benchell, Jill; Anderson, Barbara J
Abstract : Multiple sources of burden for youth with type 1 diabetes (T1D) impact key outcomes including quality of life, self‐management, and glycemic control. Professional diabetes organizations recommend diabetes care providers screen for psychosocial and behavioral challenges and implement strategies to support youth with T1D. The purpose of this article is to review the literature and recommend practical strategies medical providers can use for screening and behavioral support for youth with diabetes and their families. As part of their routine medical care, diabetes care providers are well‐positioned to identify and intervene to address emotional distress related to the burdens of living with diabetes. In collaboration with multidisciplinary team members, including psychologists and mental health professionals, medical providers may be able to successfully implement brief behavioral strategies for screening and providing emotional support.